2021
DOI: 10.1016/j.toxrep.2021.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Determination of prenatal exposure to parabens and triclosan and estimation of maternal and fetal burden

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Biological matrices were collected at various gestational ages, with urine as the predominantly measured biological matrix. A few studies measured paraben concentrations using placentae or amniotic fluid [ 28 , 29 , 30 , 31 ]. The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Biological matrices were collected at various gestational ages, with urine as the predominantly measured biological matrix. A few studies measured paraben concentrations using placentae or amniotic fluid [ 28 , 29 , 30 , 31 ]. The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…A few studies measured paraben concentrations using placentae or amniotic fluid [ 28 , 29 , 30 , 31 ]. The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ]. Early life exposure to parabens is associated with increases in the gestational weight gain (GWG) rate [ 32 ], changes in height, head, hip, or arm circumference [ 28 , 30 , 33 , 34 ], z-scores of bodyweight [ 35 ], BMI or BMI z-scores [ 31 , 36 , 37 ], and overweight status in early childhood [ 38 ], although the direction of associations depends on the type of parabens and gender ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations